Transformation of the Idrisiyyah Order: Navigating Social and Economic Challenges in the Digital Era - Fahrurrozi, Muhammad; Munandar, Siswoyo Aris (Digital Muslim Review, 2024)
This study explores the challenges and opportunities faced by The Idrisiyyah Order, a prominent Sufi order in Indonesia, in adapting to the digital era. Key challenges include preserving traditional values amidst digital influences, managing data privacy and security, and providing digital education to members with limited technological skills. The research highlights how The Idrisiyyah Order leverages digital technologies such as mobile applications and e-commerce platforms to enhance its social and economic initiatives. Using a qualitative approach with a descriptive case study design focused on The Idrisiyyah Order in Tasikmalaya, the study examines how these innovations enable the order to market local products globally, empower small and medium enterprises (SMEs), and integrate digital strategies into economic and spiritual development. Findings indicate that the order's digital initiatives promote economic empowerment, social cohesion, and spiritual education. The effective use of media for da'wah, strategic management of digital content, and adoption of crowdfunding platforms for humanitarian projects illustrate the potential of technology to enhance both material and spiritual dimensions of life. The study concludes that The Idrisiyyah Order’s approach fosters a harmonious integration of traditional practices and modern advancements, contributing to community welfare and spiritual growth.